The Implementation of Innovative Thematic Module to Improve Students Logical Thinking Ability - Widiyatmoko, Arif; Dewi, Novi Ratna; Yanitama, Arka (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2020)
The purpose of this study was to developing an innovative thematic module on basic physics course and improving students’ logical thinking ability especially in the subject of Basic Physics II. The assessment developed in this study is an inquiry-based assessment to determine the ability to think logically by the students in learning science theme